The effect of acidic residues and amphipathicity on the lytic activities of mastoparan peptides studied by fluorescence and CD spectroscopy - Leite, Natalia Bueno [UNESP]; Costa, Laiana Cristina da [UNESP]; Alvares, Dayane dos Santos [UNESP]; Santos Cabrera, Marcia Perez dos [UNESP]; Souza, Bibiana Monson de [UNESP]; Palma, Mario Sergio [UNESP]; Ruggiero Neto, João [UNESP] (Springer, 2011)
Some mastoparan peptides extracted from social wasps display antimicrobial activity and some are hemolytic and cytotoxic. Although the cell specificity of these peptides is complex and poorly understood, it is believed that their net charges and their hydrophobicity contribute to modulate their biological activities. We report a study, using fluorescence and circular dichroism spectroscopies, evaluating the influence of these two parameters on the lytic activities of five mastoparans in zwitterionic and anionic phospholipid vesicles. Four of these peptides, extracted from the venom of the social wasp Polybia paulista, present both acidic and basic residues with net charges ranging from +1 to +3 which were compared to Mastoparan-X with three basic residues and net charge +4. Previous studies revealed that these peptides have moderate-to-strong antibacterial activity against Gram-positive and Gram-negative microorganisms and some of them are hemolytic. Their affinity and lytic activity in zwitterionic vesicles decrease with the net electrical charges and the dose response curves are more cooperative for the less charged peptides. Higher charged peptides display higher affinity and lytic activity in anionic vesicles. The present study shows that the acidic residues play an important role in modulating the peptides' lytic and biological activities and influence differently when the peptide is hydrophobic or when the acidic residue is in a hydrophilic peptide.
Keywords: Mastoparan; Antimicrobial peptides; Peptide net charge; Hydrophobicity; Circular dichroism; Fluorescence spectroscopy